Métodos de Manejo de Insetos Vetores de Viroses e Broqueadores de Tomate (Lycopersicon esculentum Miller) - Grecco, Eduardo Domingos (2014)
The Lycopersicon esculentum is a solanaceous with socioeconomic benefits, but the deployment of their culture is considered high risk due to the occurrence of major pests such as insect vectors of viruses and fruit borers. Therefore, the aim of this study